Cold‐adaptive evolution at the reproductive stage in Geng/japonica subspecies reveals the role of OsMAPK3 and OsLEA9. (30th June 2022) - Lou, Qijin; Guo, Haifeng; Li, Jin; Han, Shichen; Khan, Najeeb Ullah; Gu, Yunsong; Zhao, Weitong; Zhang, Zhanying; Zhang, Hongliang; Li, Zichao; Li, Jinjie
SUMMARY: Cold stress at the reproductive stage severely affects the production and geographic distribution of rice. The Geng / japonica subpopulation gradually developed stronger cold adaptation than the Xian / indica subpopulation during the long‐term domestication of cultivated rice. However, the evolutionary path and natural alleles underlying the cold adaptability of intra‐ Geng subspecies remain largely unknown. Here, we identified MITOGEN‐ACTIVATED PROTEIN KINASE 3 ( OsMAPK3 ) and LATE EMBRYOGENESIS ABUNDANT PROTEIN 9 ( OsLEA9 ) as two important regulators for the cold adaptation of Geng subspecies from a combination of transcriptome analysis and genome‐wide association study. Transgenic validation showed that OsMAPK3 and OsLEA9 confer cold tolerance at the reproductive stage. Selection and evolution analysis suggested that the Geng version of OsMAPK3 ( OsMAPK3 Geng ) directly evolved from Chinese Oryza rufipogon III and was largely retained in high‐latitude and high‐altitude regions with low temperatures during domestication. Later, the functional nucleotide polymorphism (FNP‐776) in the Kunmingxiaobaigu and Lijiangxiaoheigu version of the OsLEA9 ( OsLEA9 KL ) promoter originated from novel variation of intra‐ Geng was selected and predominantly retained in temperate Geng to improve the adaptation of Geng together with OsMAPK3 Geng to colder climatic conditions in high‐latitude areas. Breeding potential analysis suggested that pyramiding of OsMAPK3 Geng and OsLEA9 KL enhanced the cold tolerance of Geng and promotes the expansion of cultivated rice to colder regions. This study not only highlights the evolutionary path taken by the cold‐adaptive differentiation of intra‐ Geng, but also provides new genetic resources for rice molecular breeding in low‐temperature areas. Significance Statement: In this study, we identified variants in the two genes, OsMAPK3 and OsLEA9, as conferring cold tolerance of the Geng subspecies at the reproductive stage. OsMAPK3Geng originated from Chinese Oryza rufipogon III before following two evolutionary routes during domestication. It first genetically interacts with an allele of OsLEA9KL, which harbors a novel polymorphism in its promoter in Geng, to improve jointly the cold adaptability of Geng and promote its expansion to high‐altitude regions with a colder climate. In parallel, variation in OsMAPK3Geng sequentially move northward and enhance the tolerance of Geng to lower temperatures, eventually promoting the planting of Geng in higher‐latitude areas such as northeast China. Our results provide insights into the evolutionary path of cold tolerance genes underlying the cold adaptation of intra‐ Geng and provide new genetic resources for rice molecular breeding for cold tolerance.